Edukasi Masyarakat Tentang Strategi Pengembangan Model Bisnis Syariah Dalam Meningkatkan Usaha - Rahmawati, Azizah; Purwanti, Iis; Baity, Laila Nur; Oktaviani, Laila (Lembaga Penelitian dan Pengabdian Masyarakat IAI An-Nadwah Kuala Tungkal, 2024)
This study aims to explore the impact of community education on business model development strategies on business success. Business education is an important component that can improve the knowledge and skills of entrepreneurs, especially in designing and implementing effective business models. The method used in this research is a qualitative method. In addition, this research also uses educational methods with the zoom platform which is implemented to deliver educational material to MSME players. The results showed that structured and sustainable community education on business model development strategies can improve business owners' understanding of markets, business success, and product innovation. In addition, this study found that business owners who actively participate in business education programs tend to have higher business success rates than those who do not. The implication of this study is that the government and related institutions need to strengthen business education programs as an effort to improve business competitiveness and sustainability among the community.